Capabilities and Choices: Do They Make Sen'se for Understanding Objective and Subjective Well-Being? An Empirical Test of Sen's Capability Framework on German and British Panel Data - Ruud Muffels; Bruce Headey (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
In Sen's Capability Approach (CA) well-being can be defined as the freedom of choice to achieve the things in life which one has reason to value most for his or her personal life. Capabilities are in Sen's vocabulary therefore the real freedoms people have or the opportunities available to them. In this paper we examine the impact of capabilities alongside choices on subjective and objective well-being. There is a lot of theoretical work on Sen's capability framework but still a lack of empirical research in measuring and testing his capability model especially in a dynamic perspective. The aim of the paper is to elaborate and test a "stock-flow" model measuring capabilities and choices to explain longer-term changes in well-being using 25 years of German and 18 years of British data. Three measures of well-being are constructed: life satisfaction for subjective well-being (SWB) and relative income and employment security for objective well-being (OWB). We ran random and fixed effects GLS models. The findings strongly support Sen's capabilities framework and provide new evidence on the way capabilities and choices matter for well-being. Capabilities indicated by human capital, trust, altruism and risk taking, and family, work-leisure, lifestyle and social choices show to strongly affect the three well-being indicators but their effect sizes differ largely dependent on the type of indicator used.
Keywords: D3; D31; D63; I32; J21; J24; J64; 330; Subjective and objective well-being; happiness; work-leisure choices; income security; employment security; Sens capability approach; German and British panel data; fixed effects GLS models; Capability-Ansatz; Zufriedenheit; Lebensqualität; Schätzung; Deutschland; Großbritannien